Development of a novel ground test facility for aircraft environmental control system - Chowdhury, Shafayat H.; Ali, Fakhre; Jennions, Ian K. (American Society of Mechanical Engineers (ASME), 2023)
In this article, the development and experimental investigation of a Boeing 737 aircraft environmental control system (ECS) passenger air conditioner (PACK) has been reported. The PACK is the heart of the ECS that conditions bleed air prior to supplying it to the cabin and avionics bay. Its capability to mask fault occurrences has resulted in increased unscheduled maintenance of the system. As such it has been a key research topic to understand PACK performance characteristics in order to support an accurate diagnostic solution. This article is a continuation of the authors’ work on the development of a systematically derived PACK simulation model and reports the overall development and qualification of a novel in situ ground test facility (GTF) for the experimental investigation of a B737-400 aircraft PACK under various operating modes, including the effect of trim air system. The developed GTF enables the acquisition of the temperature, pressure, and mass flow data throughout the PACK. The overall process of instrumentation selection, installation, sensor uncertainty, and testing in terms of data repeatability and consistency has been reported. The acquired data are then employed to conduct verification and validation of the SESAC (simscape ECS simulation under all conditions) simulation framework. The reported research work therefore enables the advancement in the level of scientific understanding corresponding to the ECS PACK operation under real operating conditions, and therefore supports the development of a robust simulation framework for ECS fault diagnostics at the system level.
Keywords: Aerospace Heat Transfer; Experimental/Measurement Techniques; Thermal Systems